Managing complex projects - Turner, Neil; Davis, Kate; Cantarelli, Chantal C. (CRC Press, 2024)
Complexity is an issue that affects all projects. Project managers know this, but it can be difficult to express the realities they face in a language that others can easily grasp. In this chapter we draw on research that identifies three different kinds of project complexity – structural, socio-political, and emergent, and look at practical response techniques to these. We offer a complexity framework to help managers deal with these challenges. We then show how this can be used both as a problem-solving tool, and also as a method to draw out lessons learned at gate reviews or at the completion of the work.
Keywords: Computer Science; Economics; Finance; Business & Industry; Engineering & Technology